Clinical outcomes with on-label and off-label use of the transcatheter heart valve in the United States - Lardizabal, Joel A.; Macon, Conrad J.; O'Neill, Brian P.; Singh, Vikas; Martinez, Claudia A.; Alfonso, Carlos; Cohen, Mauricio G.; Williams, Donald B.; O'Neill, William W.; Heldman, Alan W. (Catheterization and cardiovascular interventions, 2014)
Objective We explored the efficacy, safety, and clinical consequences of on‐label and off‐label transcatheter aortic valve replacement (TAVR) in the real‐world setting. Background The transcatheter heart valve (THV) was initially approved only for transfemoral (TF) delivery (on‐label use) during TAVR in inoperable patients with severe aortic stenosis (AS). Because of lack of alternative options in TAVR‐eligible patients with inadequate TF access, other routes have been utilized for THV implantation (off‐label use), outcomes of which were previously unknown. Methods Consecutive patients with severe inoperable AS who underwent clinical TAVR at our site were enrolled in a prospective database. Fifty subjects underwent TF‐TAVR (on‐label group), while non‐TF routes were utilized in 60 subjects (off‐label group). Procedural events, 30‐day clinical outcomes, and 1‐year all‐cause mortality data were analyzed. Results Technical device success was similar between on‐label and off‐label groups (88% vs. 87%, respectively; P = 0.92), as was the incidence of procedural complications and 30‐day clinical events. The on‐label group had lower 1‐year all‐cause death rate (12%) compared to the off‐label group (32%; P = 0.02). The 1‐year all‐cause mortality in the off‐label group was comparable to published clinical trial and registry data on TAVR, and appeared lower than historical outcomes with conservative medical therapy. Conclusion On‐label use of the THV in the real‐world setting was associated with favorable survival outcomes compared to off‐label TAVR and historical data. Off‐label use of the THV appeared to be safe and effective when used in select patients with inoperable AS who are not eligible for TAVR via TF approach. © 2014 Wiley Periodicals, Inc.